Perlindungan Hukum Terhadap Penjatuhan Sanksi Pidana Kepada Anak Sebagai Pelaku dalam Penyalahgunaan Tindak Pidana Narkotika - Hasan, Zainudin; Emco, Andika Putra; Pratama, Asep; Arlintang, Alfondo Deofani; Febriansyah, Fahmi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This research was made by Law Protection needs based on Child Human Rights, which every child has right to gain a bright future. Also to review Law Protection for child who did a crime based on Constitutional Law. This research made to understand the legal protection provided to child who are involved in narcotics crime. Based on the description above, there is a problem formulation that is, what is the form of legal protection for children as perpetrators in the abuse of narcotics crimes. Then what are the factors inhibiting legal protection for children as narcotics abusers. The method used is normative juridical research method, that is research on secondary data. With this research done, there’s a hope about Law Protection for child who did a Criminal act have large area so it will become more effective and do preventive acts to prevent the same criminal act repeated and the similar act won’t be repeated and also it can grow up on handling a child as a criminal act to become better in the future.